2022
DOI: 10.1111/fwb.13955
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating environmental DNA metabarcoding as a survey tool for unionid mussel assessments

Abstract: Freshwater unionid mussels are a taxa‐rich group of bivalves that play a critical role in maintaining freshwater ecosystems, but are heavily imperilled due to anthropogenic influences. Environmental DNA (eDNA) provides potential benefits for the monitoring of unionids through higher detection sensitivity, lower costs, less intrusion on the environment, and added advantages for sampling challenging and remote habitats. We compare an extensive mussel rescue survey conducted as part of the demolition of a dam wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Our objective was to evaluate the use of eDNA as a sampling technique for a well-studied assemblage of freshwater mussels in the biologically diverse Sipsey River system in the southeastern USA. Four recent studies have demonstrated the effectiveness of metabarcoding to identify freshwater mussel species in France, Switzerland, Italy, Morocco ( Prié et al, 2021 ), Virginia, USA ( Klymus et al, 2021 ), Ontario, Canada ( Coghlan et al, 2021 ), and Ohio, USA ( Marshall et al, 2022 ). However, these studies describe a range of agreement of species detection from eDNA compared with traditional surveys ranging from 40% to 58% agreement in Virginia/Tennessee ( Klymus et al, 2021 ) to 92% in Ohio ( Marshall et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our objective was to evaluate the use of eDNA as a sampling technique for a well-studied assemblage of freshwater mussels in the biologically diverse Sipsey River system in the southeastern USA. Four recent studies have demonstrated the effectiveness of metabarcoding to identify freshwater mussel species in France, Switzerland, Italy, Morocco ( Prié et al, 2021 ), Virginia, USA ( Klymus et al, 2021 ), Ontario, Canada ( Coghlan et al, 2021 ), and Ohio, USA ( Marshall et al, 2022 ). However, these studies describe a range of agreement of species detection from eDNA compared with traditional surveys ranging from 40% to 58% agreement in Virginia/Tennessee ( Klymus et al, 2021 ) to 92% in Ohio ( Marshall et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four recent studies have demonstrated the effectiveness of metabarcoding to identify freshwater mussel species in France, Switzerland, Italy, Morocco ( Prié et al, 2021 ), Virginia, USA ( Klymus et al, 2021 ), Ontario, Canada ( Coghlan et al, 2021 ), and Ohio, USA ( Marshall et al, 2022 ). However, these studies describe a range of agreement of species detection from eDNA compared with traditional surveys ranging from 40% to 58% agreement in Virginia/Tennessee ( Klymus et al, 2021 ) to 92% in Ohio ( Marshall et al, 2022 ). Similarly, our eDNA results were broadly consistent with the data from traditional quadrat-based field surveys, although both community eDNA and conventional sampling detected some species that the other method did not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early freshwater mussel eDNA studies primarily used species‐specific assays, although more recently, studies have emerged using metabarcoding approaches to identify unionid mussel communities (Coghlan et al, 2021; Klymus et al, 2021; Marshall et al, 2022; Prié et al, 2021). These metabarcoding studies have included development of multiple metabarcoding primers and have demonstrated that high proportions of the known mussel community can be detected using eDNA (e.g., >80% (Coghlan et al, 2021) and 91% (Marshall et al, 2022)). Both species‐specific and metabarcoding approaches face similar challenges, including the need for numerous field samples and replicates to obtain sufficient detection rates when typical eDNA filtering approaches are employed (Marshall et al, 2022).…”
Section: Introductionmentioning
confidence: 99%